Design and Build Online Store Website bicycle store KawanKita - Eddy Sukamto; Albertus Dwiyoga Widiantoro; Erdhi Widyarto Nugroho (Journal of Business and Technology, 2023)
E-commerce websites are important to implement in small business processes. To facilitate the transaction process, this research was carried out so that the transaction process between sellers and buyers became more effective and efficient. The purpose of this research is to attract consumers with an attractive and user-friendly website to buy products from the KawanKita bicycle shop so that it has an impact on increasing sales, the analytical method process is applied to implementation. The development method used is "waterfall" where step by step are related to one another. That way the discussion process with the KawanKita store owner resulted in a website business process design, ER Diagram, UI and UX design for display, for the platform framework used is Node Js as the back-end and React Js as the front-end. In terms of storing data, this website uses Firebase as a data storage provider and as a hosting provider. KawanKita bicycle shop business owner. So that this research produces a website that makes it easier for consumers and sellers in the transaction process, the appearance of the website is good at displaying the goods being sold. From the process of business analysis, ERD creation, user UI and UX design, to the creation of this website, from the appearance to the functions in each of its features, all have received a positive response from the public.